ANALISIS PENERAPAN WARNA PADA INFOGRAFIS EDUKASI PENGELOLAAN SAMPAH PLASTIK UNTUK ANAK USIA DINI - Andi Magfirah Nugraheni; Wulan Madani Aisyiyah; Nora Hafildah; Fia Izzah Maylinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Color is one of the most immediately perceived visual elements in graphic design, yet its application in educational infographics for early childhood is often treated intuitively rather than systematically. This study focuses on how color is applied in an educational infographic designed for early childhood, using a plastic waste management campaign infographic at Bunda Ganesa Kindergarten Bandung as the case study. Using a qualitative approach grounded in color theory and color psychology, this study analyzes how hue, contrast, and color schemes are applied across an infographic's visual hierarchy, typography, iconography, and background, and how these applications influence children's attention, comprehension, and retention. Data were examined through descriptive analysis and a color-comparison matrix applied to the infographic's elements. The findings indicate that warm, high-contrast colors applied consistently across visual hierarchy and a semantically consistent color-coding system for icons improve legibility and support faster recognition among children aged 4-6 years. This study contributes a practical framework for applying color in visual communication design for early-childhood educational infographics in general, beyond the specific campaign context used as its case study.Keywords: Color, Infographic, Early Childhood, Education, Plastic Waste.